IMPLEMENTATION OF HIV AIDS PREVENTION POLICY IN SUKABUMI REGENCY - Suhendar, Risma Sri Mulyani; Nur, Tuah; Sampurna, Rizki Hegia (DIA: Jurnal Administrasi Publik, 2025)
The title of this research is "Implementation of HIV/AIDS Prevention Policy in Sukabumi Regency." This research focuses on implementing the HIV/AIDS prevention program by the AIDS Prevention Commission (KPA) of Sukabumi Regency. The research problem is the increasing cases of HIV/AIDS in the Sukabumi Regency. The method is descriptive qualitative, with data collection through observation, interviews, and documentation. The theory used is Van Meter and Van Horn (1975). Informants were determined using the non-probability sampling technique and snowball sampling method. The results showed that the implementation of the HIV/AIDS prevention program in Sukabumi Regency has not been optimal. Communication between organizations has been quite good, with clear roles. However, human resources still need to be improved compared to the wide area that needs to be handled, and the government fully supports this program. In addition, in terms of economic, social, and political aspects, differences in interests still hinder good partnerships at the village government level.